Angola. Os Símbolos do Poder na Sociedade Tradicional - M. L. Rodrigues de Areia (Outros Títulos, 2019)
Power neither exists nor stands without symbols. In a space where awareness of ethnic diversity is increasingly tending to revalue the dynamics of the traditional, it is not merely academic to provide a glimpse of the rich symbology elaborated by the different forms of organizing traditional power. This will also be one of the many concrete ways to "gather data to define and illustrate the cultural identity of peoples Bantu, of yesteryear and today," aim "Bantu International Center for Civilization", an organization recently created to study and preserve the cultural heritage common to Africa's Banta. Angola is a field particularly rich in cultural traditions of this kind. In its territory numerous principalities and families were developed in which the power exercised under varied forms of royalty. This diversity sought to account for the selection of exposed objects; In writing texts, however, it was not possible to go beyond the most representative groups: the Kongo (in particular the Woyo subgroup) and the Ovimbundu. Suffering from the vicissitudes of different African histories (pre-colonial, colonial, post-colonial) the symbols of power survived even when confined only to their ritual component. There was even an enlargement determined by the incorporation of acculturated symbols, namely religious ones (crucifix and rosary, among others). The different anthropological collections around the world are in some cases unique testimonies of this "show of power" that only disappeared in appearance as it is still very much alive inside. Some testimonies of these symbols were collected less than half a century ago (M. A. F. de Oliveira), others are reborn from an apparent state of lethargy taking on new expression (see in particular the growing claim of the role of women in the transformation of Angolan society and the female component of power in the tradition of Kongo - M. L. Rodrigues de Areia); still others manifest themselves in the consistent demand that the holders of power assume themselves as defenders of life and what conditions it - a clear reflection of the traditional concept of the charismatic chief (sacred royalty) to whom the fertility of the fields such as that of women was imputed. women, the occurrence of rain as the scourge of drought. The analysis of the testimonies of traditional royals, which are of the past, must not only raise, besides the inference of the symbolization mechanisms resulting from social structures, also from the past, the ever- present question of the "systems of power and the conditions of its formation and transformation" O. Houart ); on the one hand, they provide the evocation of a past that reaffirms itself as an element of cultural identity; on the other, they justify a new discourse on the exercise of power. [M. L. RODRIGUES DE AREIA]